The effect of heat treatment at 1200 °C on microstructure and mechanical properties evolution of AlCoCrFeNiSiYHf high entropy alloys. (June 2022) - Yu, Jingyi; Mu, Rende; Qu, Shiyu; Cai, Yan; Shen, Zaoyu
Abstract: AlCoCrFeNiSiYHf high entropy alloys were designed and prepared as new bond-coat material of thermal barrier coatings to meet the requirement of higher thrust-to-weight ratio aero turbine engines. The microstructural and componential evolution of AlCoCrFeNiSiYHf high entropy alloys was studied under 1200 °C to evaluate the potential applications in thermal barrier coatings system. Crystal texture transfer and phase structure were detected to analyze the relationship between element diffusion and phase transformation. The results indicate that heat, which transferred from muffle furnace, might be the driving force for element diffusion and homogenization. An FCC to BCC phase transformation in AlCoCrFeNiSiYHf high entropy alloy is observed after 1 h exposure in 1200 °C. After heat treatment, all mechanical properties we tested have been improved in varying degrees. Highlights: AlCoCrFeNiSiYHf high-entropy alloys were prepared by vacuum levitation melting. Heat treatment promoted the homogenization of HEAs leading to FCC to BCC phase transformation. The theoretical study about CTE indicates that bond value model is suitable for HEAs.